ECONOMIC EFFICIENCY OF THE USE OF PRODUCTION FACTORS IN THE HOUSEHOLD INDUSTRY OF TEMPEH CHIPS IN WONOGIRI REGENCY - Renie Nandar Agustina; Wiwit Rahayu; Umi Barokah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
This research aims to determine the cost, revenue, influence of production factors, and economic efficiency of tempeh chips in Wonogiri Regency. The primary method of analysis is descriptive and analytical. The proportional random sampling method determined the process of determining the location by purposive sampling and 30 samples. Data analysis methods include (1) Cost, Revenue, and Profit Analysis; (2) Analysis of Multiple Linear Regression in the Cobb-Douglass Production Function; (3) Economic Efficiency Analysis. The results showed an average total cost of Rp. 22,550,435.53 per month, a revenue of Rp. 27,828,488.57 per month, and a profit of Rp. 5,278,053.04 per month. Soybean and flour production factors partially have a significant effect on the production of tempeh chips. The results of the economic efficiency analysis showed that the use of soybeans had not achieved economic efficiency while the use of flour was inefficient. Economic efficiency in the tempeh chips industry business can be improved by increasing the factor of soybean and reducing the use of flour.